Анализа корелације нивоа ЦЦЛ4, ТРАЦП-5б и ХПДР2 у серуму са негативним исходима код остеопорозе после менопаузе (ОМ): Серумски CCL4, TRACP-5b и HPDR2 код ПМОП-а - Zhu, Kejia; Sun, Jiaqu; Wang, Biao; Xing, Fei; Zhang, Hui; Deng, Tao; Wang, Junqing; Zhang, Yuqi; Yan, Dusong; Nie, Yong (Journal of Medical Biochemistry, 2026)
Objective To determine the predictive efficacy of measuring fibroblast growth factor 23 (HPDR2) in postmenopausal individuals with osteoporosis, tartrate-resistant acid phosphatase 5b (TRACP-5b), and serum macrophage inflammatory protein-1 β (CCL4) for fractures. Methods The osteoporosis group consisted of 242 postmenopausal individuals with osteoporosis who were admitted to the hospital between January 2023 and January 2025. There were two groups of patients: 108 patients with fractures and 134 patients without. The decreased bone mass group (164 patients) and the control group (130 patients) were composed of postmenopausal women who were diagnosed with decreased bone mass and normal bone mass in the hospital during the same time period. The levels of serum CCL4, TRACP-5b and HPDR2 in each group were compared. The predictive value of serum CCL4, TRACP-5b, and HPDR2 detection for fractures in postmenopausal patients with osteoporosis was assessed using univariate and multivariate analysis on the influencing factors of fractures in patients with osteoporosis. The relationships between the levels of serum CCL4, TRACP-5b and HPDR2 and the severity of fractures were analyzed. Results The levels of serum CCL4, TRACP-5b and HPDR2 in the osteoporosis group were significantly greater than those in the decreased bone mass group and the control group (P<0.01), and the reduced bone mass group’s serum CCL4, TRACP-5b, and HPDR2 levels were considerably higher than the control group’s (P<0.01). The fracture group had significantly greater serum levels of HPDR2, TRACP-5b, and CCL4 than the nonfracture group (P<0.01). Multivariate analysis revealed that serum CCL4>719.75 pg/mL, TRACP-5b>6.90 U/L and HPDR2>247.35 pg/mL were risk factors for fractures in postmenopausal patients with osteoporosis (P<0.01). The levels of serum CCL4, TRACP-5b and HPDR2 are highly effective at predicting fractures in patients with osteoporosis (P<0.01). The combined detection sensitivity of the three indicators was 90.0%, the specificity was 89.7%, and the area under the curve (AUC) was 0.949. The AUC was significantly greater than that of CCL4 (Z=3. 415, P<0.01), TRACP-5b (Z=3.814, P<0.01), and HPDR2 (Z=3.986, P<0.01) were detected as individual indicators. However, the AUC of each individual indicator did not change statistically significantly (P>0.05). Conclusion Serum CCL4, TRACP-5b and HPDR2 are involved in the occurrence and development of postmenopausal osteoporosis. The detection of their levels has high value in predicting fractures in postmenopausal osteoporosis patients.